VISUALIZATION SETTING AS TIMER APPOINTMENT IN THE MOVIE “AACH AKU JATUH CINTA” - Sagita, Rio Putra; DA, NRA. Candra (Capture : Jurnal Seni Media Rekam, 2018)
This study examines the film “Aach…Aku Jatuh Cinta” (Aach...I Fall in Love). This study aims to find out the visualization of the setting as a timepiece in the film “Aach…Aku Jatuh Cinta” through the size of the image. The type of research used is descriptive qualitative research. The selection of samples in this study was carried out by purposive sampling technique. Data collection is done by observation and interviews, while data analysis is done through the stages of data reduction, data presentation, and drawing conclusions and verification. Research focuses on setting as a timepiece visualized in the film “Aach…Aku Jatuh Cinta” through the size of the image. The results of the research of “Aach…Aku Jatuh Cinta” show the time settings are divided into three sequences, the settings that appeared in 1970, 1980 and 1990